DEVELOPMENT OF PLAYDOUGH TREASURE HUNT GAME MEDIA TO TRAIN FINE MOTOR SKILLS IN CHILDREN WITH MENTAL DISABILITIES (International Journal of Cultural and Social Science, 2026)
This study aims to develop a playdough treasure hunt game medium that is feasible for use in learning activities to train the fine motor skills of children with intellectual disabilities, as well as to determine students’ and teachers’ responses to the developed medium. This study employed a Research and Development (R&D) method using the 4D model, which consists of the define, design, develop, and disseminate stages. The research subjects consisted of four third-grade students with mild intellectual disabilities at SLBN Syach Abdurrauf. Data were collected through questionnaires and observation. The data were analyzed using percentage techniques to determine the feasibility level of the medium. The results showed that the playdough treasure hunt game medium was categorized as highly feasible based on the validation results from material experts and media experts. In addition, students’ responses to the use of the medium were categorized as good, as indicated by their interest, active participation, and enthusiasm during the learning activities. Teachers’ responses were also categorized as very good, indicating that the medium was easy to use and appropriate to the learning needs. Therefore, the playdough treasure hunt game medium can be used as an alternative learning medium to support activities for training the fine motor skills of children with intellectual disabilities through enjoyable and concrete activities.